Optimization of the Bhabinkamtibmas Sambang in the Prevention of Motor Vehicle Theft to Realize Harkamtibmas at the Tegal City Police - FIRMANSYAH ALVIAN RAMADHAN (Indonesian Journal of Police Studies, 2022)
ABSTRACT Optimization of the Bhabinkamtibmas Sambang in the Prevention of Motor Vehicle Theft to Realize Harkamtibmas at the Tegal City Police Firmansyah Alvian Ramadhan, 18.159, alvianfirmansyah99@gmail.com This writing is motivated by the high number of motor vehicle theft crimes in the jurisdiction of the Tegal City Police. The Bhayangkara Supervisor of Public Order and Security (Bhabinkamtibmas) is the spearhead of the National Police in preventing crime. Bhabinkamtibmas has carried out daily visits, but the implementation has not been optimal because Bhabinkamtibmas only focuses on handling Covid-19. This writing aims to describe the implementation of sambang by Bhabinkamtibmas and find optimization of the implementation of sambang by Bhabinkamtibmas in preventing motor vehicle theft in order to realize Harkamtibmas at Polres Tegal City. The theory that is used as an analytical in this writing is management theory. While the concepts used are the concept of Bhabinkamtibmas, sambang, optimization, crime prevention, motor vehicle theft, and maintenance of public security and order (Harkamtibmas). This study uses a qualitative approach and data collection through interviews, observations, and document studies. The research was carried out in the jurisdiction of the Tegal City Police. The results of the study found that the implementation of the Bhabinkamtibmas sambang in order to prevent burglary was not optimal because obstacles were found such as the absence of clear targets for the implementation of the sambang, Bhabinkamtibmas was still included in the picket function, the implementation was still not in accordance with the National Police Chief Regulation Number 7 of 2021 concerning Bhabinkamtibmas, and for monitoring the implementation of the sambang. Bhabinkamtibmas only reports WhatsApp for the results of the implementation of activities. Analysis of the optimization of the Bhabinkamtibmas chat in preventing theft according to the theory of elements of management found that most of the Bhabinkamtibmas have not implemented Dikjur, the material presented is still focused on handling Covid-19, the target of the visit is only the community, and facilities and infrastructure are still lacking for Bhabinkamtibmas. Based on the results of the research, the writer's problem solving includes making a pocket book on the implementation of the Bhabinkamtibmas visit and making a brochure for the prevention of theft of crime to be used as a guide for Bhabinkamtibmas when carrying out the visit.